Photography as a Witness of Theatre - Dondero, Maria (Recherches sémiotiques / Semiotic Inquiry, 2008)
My paper investigates the meeting of theatre and photography in ‘theatre photography’. Recognizing that both art forms can determine theoretical and philosophical views on representation and self-representation, I aim to compare their visual strategies and the way they construct point of view. In the process several questions are raised: do qualities of photographs belong to objects photographed or to photographs themselves? How important is the object that ‘triggers’ the view? Should the theatre photographer place his camera anywhere? What of framing?In the second section I offer an analysis of photographs taken by Roger Pic in 1957 during the Paris performance of Brecht’s Mother Courage and Her Children by the Berliner Ensemble. This analysis seeks to demonstrate that theatre photography, which often seen as an example of documentary photography, can reach artistic status, provided it relies on enunciative strategies that express what cannot otherwise be photographed in a ‘direct’ manner, namely the characters’ words and emotions.